Effects of Chemokine Ligand 2 on Budding of Bovine Foamy Virus - Rui Li; Zhaohuan Wang; Chenxi Liu; Wentao Qiao; Juan Tan (Viruses, 2023)
The endosomal sorting complex required for transport (ESCRT) machinery is essential for the budding of retroviruses such as human immunodeficiency virus (HIV) and bovine foamy virus (BFV), which rely on their late domain to recruit ESCRT complexes to facilitate budding. However, the impact of intracellular host proteins on BFV budding remains poorly understood. In this study, we aimed to investigate the impact of CCL2 on BFV budding and interactions with key host proteins. Our results indicate that CCL2 promotes BFV budding in an ALG-2-interacting protein X (Alix)-dependent manner by enhancing the interaction between Alix and BFV Gag (BGag). Notably, we found a link between Alix, BGag and CCL2, with Alix mediating the interaction between the latter two. Furthermore, we observed that natural host bovine CCL2 also has a facilitating role in the budding process of BFV, similar to human CCL2. Taken together, these results demonstrate that CCL2 promotes BFV budding by enhancing the Alix-BGag association.